Voices on Joyce - Fogarty, Anne 1958-; O'Rourke, Fran 1951- (Univ. College of Dublin Press, 2015)
Joyce's writing is celebrated for its encyclopaedism and multi-facetedness; it accommodates readings from a wide variety of perspectives. This collection of essays gathers to get interpretations by scholars working in a wide range of disciplines, including music, history, literature, philosophy, languages, sport, geography, economics, drama studies and law. Their readings uncover the plural dimensions of Joyce's writings and show the degree to which they assemble and mesh together knowledge and insight from numerous different disciplines and spheres of knowledge. The essays are composed by present and former UCD academics and as such constitute a unique reckoning with the legacy of Joyce by members of his alma mater